Miary efektywności w zakładach opieki zdrowotnej - Jaworzyńska, Magdalena (The Measurements of Efficiency within Medical Centers, 2007)
The efficiency in health service refers to both macro- and micro-efficiency - that is allocation of resources for the health services. One of the measurements of efficiency within medical centers is the cost-effect analysis. The aim of this article is to present different forms of both economic and medical effect evaluation within the medical centers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 252-259